2023
DOI: 10.3389/fimmu.2023.1275408
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into cGAS-STING pathway in ischemic stroke: from pre- to post-disease

Xiaoqi Ma,
Dan Xin,
Ruining She
et al.

Abstract: Ischemic stroke, a primary cause of disability and the second leading cause of mortality, has emerged as an urgent public health issue. Growing evidence suggests that the Cyclic GMP-AMP synthase (cGAS)- Stimulator of interferon genes (STING) pathway, a component of innate immunity, is closely associated with microglia activation, neuroinflammation, and regulated cell death in ischemic stroke. However, the mechanisms underlying this pathway remain inadequately understood. This article comprehensively reviews th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 233 publications
0
1
0
Order By: Relevance
“…It has also been claimed that COVID-19 mRNA vaccines contain excessive amounts of residual bacterial DNA, including spike encoding DNA sequences, packaged in the LNPs and thus resistant to DNase I and that billions to hundreds of billions of DNA molecules can be present per dose of vaccine [50]. DNA contamination may be prothrombotic, particularly for fragments with high GC contents [147,148]. It has also been suggested that getting the plasmids out of the E. coli, may result in residual bacterial endotoxin, in the vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been claimed that COVID-19 mRNA vaccines contain excessive amounts of residual bacterial DNA, including spike encoding DNA sequences, packaged in the LNPs and thus resistant to DNase I and that billions to hundreds of billions of DNA molecules can be present per dose of vaccine [50]. DNA contamination may be prothrombotic, particularly for fragments with high GC contents [147,148]. It has also been suggested that getting the plasmids out of the E. coli, may result in residual bacterial endotoxin, in the vaccines.…”
Section: Discussionmentioning
confidence: 99%